Regulatory T-Cell Therapy in Liver Transplantation and Chronic Liver Disease - Hann, Angus; Oo, Ye H.; Perera, M. Thamara P. R. (Frontiers in Immunology, 2021)
The constant exposure of the liver to gut derived foreign antigens has resulted in this organ attaining unique immunological characteristics, however it remains susceptible to immune mediated injury. Our understanding of this type of injury, in both the native and transplanted liver, has improved significantly in recent decades. This includes a greater awareness of the tolerance inducing CD4+ CD25+ CD127low T-cell lineage with the transcription factor FoxP3, known as regulatory T-Cells (Treg). These cells comprise 5-10% of CD4+ T cells and are known to function as an immunological “braking” mechanism, thereby preventing immune mediated tissue damage. Therapies that aim to increase Treg frequency and function have proved beneficial in the setting of both autoimmune diseases and solid organ transplantations. The safety and efficacy of Treg therapy in liver disease is an area of intense research at present and has huge potential. Due to these cells possessing significant plasticity, and the potential for conversion towards a T-helper 1 (Th1) and 17 (Th17) subsets in the hepatic microenvironment, it is pre-requisite to modify the microenvironment to a Treg favourable atmosphere to maintain these cells’ function. In addition, implementation of therapies that effectively increase Treg functional activity in the liver may result in the suppression of immune responses and will hinder those that destroy tumour cells. Thus, fine adjustment is crucial to achieve this immunological balance. This review will describe the hepatic microenvironment with relevance to Treg function, and the role these cells have in both native diseased and transplanted livers.